If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -1Y = 2a + -4y Solving 6 + -1Y = 2a + -4y Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1Y = 2a + -6 + -4y Combine like terms: 6 + -6 = 0 0 + -1Y = 2a + -6 + -4y -1Y = 2a + -6 + -4y Reorder the terms: -1Y = -6 + 2a + -4y Divide each side by '-1'. Y = 6 + -2a + 4y Simplifying Y = 6 + -2a + 4y
| -3(5-8k)=23+5k | | 0.3(x+40)-0.07(x-20)=6.5 | | X+8=0(x) | | (2X-1)(3X)=0 | | =7-4+3*0+1 | | t^2-6t+25=0 | | 0.8x-1.5=4.3x+1.9 | | (3X-2)(2X)=0 | | 5x+25=8x-2 | | n-7=-5+2n-1+2 | | (3x-2)(x+5)=14x-8 | | ln(4x)=61 | | 67=-98+5x | | 12y^2+7y+8= | | -10-6n=-52 | | (2x^2)-3x+3=0 | | 96=1.6x | | 7-2+x=5-2 | | 6t^2-24t+16=0 | | 13y=4x | | 3x-2+10= | | 3+3*6-2=x | | 0.3(x+40)-0.07(x-20)=8.8 | | -6(m-8)=-2m | | 13y=9x | | X+2x=30(x) | | -3n+7-2n=-13 | | 8x+8+3y=36 | | 5(y+3)-4(1-5y)=-39 | | 17=8x+1-4x | | 4y-4x^3=0 | | 18/-3=6 |